2011
DOI: 10.5251/abjna.2011.2.6.880.886
|View full text |Cite
|
Sign up to set email alerts
|

An infiltration model development and evaluation for pitcher irrigation system

Abstract: Infiltration models are based on quantitative relationships among variables that are developed analytically, or from a spectrum of infiltration data that could be fitted into the equation. An attempt was made to begin the development of a mathematical (infiltration)m model using the assumptions of Hillel and Gardner (1969; 1970), incorporating the assumptions of Green and Ampt (1911) and Philip (1957a;1957c). The model developed in this study used Pitcher (pot) and soil properties, as well as the time of infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Researcher described the salt tolerance of five cultivars of Capsicum annuum L and the variety NMCA 10652 had the highest survival percentage at 100% in the 4.1 dS m-1 treatment, followed by 'Early Jalapeno', 'Nu-Mex Sweet', Pimienta De Chiera', 'Santa Fe Grande', 'Golden Treasure', and 'Nu-Mex Joe E [21]. Scientist found that the highest dry chili yields of 8.12 and 20.78 q ha-1 were obtained from nonsaline canal water followed by two applications of non-saline water alternating with one saline water with 7.30 and 20.38 q ha-1 respectively [22]. Saline (well) water irrigated plants yielded 3.99 and 11.72 q ha-1 respectively, which represented yield reductions of 50.8% and 43.6%, respectively as compared with nonsaline.…”
Section: Effect Of Clay Pot Irrigation On Crops and Soilmentioning
confidence: 99%
“…Researcher described the salt tolerance of five cultivars of Capsicum annuum L and the variety NMCA 10652 had the highest survival percentage at 100% in the 4.1 dS m-1 treatment, followed by 'Early Jalapeno', 'Nu-Mex Sweet', Pimienta De Chiera', 'Santa Fe Grande', 'Golden Treasure', and 'Nu-Mex Joe E [21]. Scientist found that the highest dry chili yields of 8.12 and 20.78 q ha-1 were obtained from nonsaline canal water followed by two applications of non-saline water alternating with one saline water with 7.30 and 20.38 q ha-1 respectively [22]. Saline (well) water irrigated plants yielded 3.99 and 11.72 q ha-1 respectively, which represented yield reductions of 50.8% and 43.6%, respectively as compared with nonsaline.…”
Section: Effect Of Clay Pot Irrigation On Crops and Soilmentioning
confidence: 99%
“…A number of recent studies (Qiaosheng et al, ; Siyal et al, ; Siyal and Skaggs, ; Saleh and Setiawan, ; Usman et al, ; Al‐Mohammed, ) have examined patterns of soil wetting by buried pots or porous pipes to find the most adequate position and distribution of these irrigation emitters. On the other hand, Abu‐Zreig et al .…”
Section: Introductionmentioning
confidence: 99%